The 2019 Presidential Election in Nigeria: an analysis of the voting pattern, issues and impact - Sule, Babayo (Penerbit Universiti Kebangsaan Malaysia, 2019)
The 2019 Presidential Election is one of the most keenly and closely contested in the history of Nigerian Presidential Elections since the colonial and post-independence period. The election was heralded with tensions, accusations and counter-accusations, intense campaign, trade of blames by the ruling and major opposition parties and other related issues. This study examined the process of the conduct of the 2019 Presidential Election, the outcome and analysis of the voting pattern and its implications. The work adopted both primary and secondary sources of data. The primary source is the direct participant observation where the author was part of the process of the election as a collation officer for the Presidential Election in one of the local governments in Nigeria. The research also observed directly on a live broadcast the presentation of the results by the state returning officers where the results were collected and used for analysis. The secondary sources include the use of books, journals and internet sources. The data obtained was presented in a thematic form using tables and statistical interpretations. The research discovered that the outcome of the 2019 General Election continued to reflect the voting pattern in Nigeria where ethno-religious and regional affiliations determine how the electorates choose their President even though, the two major contenders this time emerged from the same region unlike the previous situations. The research recommends that there is a need for massive enlightenment among the electorates towards choice of leaders based on performance and not sentiments.